[18F]FDG hypometabolism precedes cognitive impairment in rats recovered from severe systemic inflammation. (1st February 2022) - Bellaver, Bruna; da Silva, Eduarda J.F.; da Rocha, Andreia Silva; Ferreira, Pamela C.L.; Venturin, Gianina Teribele; Greggio, Samuel; da Costa, Jaderson Costa; Souza, Diogo O.; Zimmer, Eduardo R.
Abstract: Background: Individuals who survive a severe systemic inflammatory episode are at higher risk to develop cognitive impairment. In this context, neuroinflammation has been considered a key player in Alzheimer's disease (AD). However, the mechanisms behind inflammation‐driven cognitive impairment/neurodegeneration are not elucidated. Here, we aimed at investigating the long‐term consequences of a severe systemic inflammatory episode on brain energy metabolism. We hypothesized that brain energetic metabolism does not completely recover from a systemic inflammatory episode, which could act as a trigger for neurodegeneration. Method: Wistar rats (90 days old) were submitted to cecal ligation and perforation surgery (CLP; a model of sepsis) and short‐term memory was assessed 30 and 120 days later through the object recognition test. Brain glucose metabolism was evaluated in vivo via micro‐PET [ 18 F]FDG. Result: Whole brain [ 18 F]FDG hypometabolism was observed in sepsis group after 30‐days recovery period (sham SUVr = 1.37 ± 0.09; sepsis SUVr = 1.27 ± 0.15). Percentage of change and t‐statistical maps revealed a peak of ∼17% in the hippocampal area (peak t = 3.17). When brain regions were analyzed, a significant [ 18 F]FDG hypometabolism was detected in the hippocampus and striatum of sepsis‐induced rats. The evaluation of [ 18 F]FDG metabolism in rats 120 days after CLP demonstrated a persistent brain hypometabolism (sham SUVr = 1.34 ± 0.10; sepsis SUVr = 1.19 ± 0.14). Regional analysis evidenced a significant decrease in [ 18 F]FDG uptake in the hippocampus, frontal and temporoparietal cortices, hypothalamus and cerebellum. Voxelwise analysis did not find differences between sepsis groups 30‐ and 120‐days post‐CLP. Despite the brain hypometabolism being observed 30‐days after induction of systemic inflammation, no cognitive deficit was evident at this point. An impairment in short‐term memory was observed 120‐days post‐CLP. Conclusion: These results demonstrate that an episode of severe systemic inflammation causes long‐term brain metabolic disturbances and cognitive impairment. Interestingly, [ 18 F]FDG hypometabolism can be detected earlier than behavioral alterations, suggesting a link between peripheral inflammation and cognitive decline/neurodegeneration.